Pathways Relating the Neurobiology of Attachment to Drug Addiction - Strathearn, Lane; Mertens, Carol E.; Mayes, Linda; Rutherford, Helena; Rajhans, Purva; Xu, Guifeng; Potenza, Marc N.; Kim, Sohye (Frontiers in Psychiatry, 2019)
Substance use disorders constitute a significant public health problem in North America and worldwide. Specifically, substance addictions in women during pregnancy or in the postpartum have adverse effects not only on the mother, but also on mother-infant attachment and the child’s subsequent development. Additionally, there is growing evidence suggesting that parental addiction may be transmitted intergenerationally, where the child of parents with addictions is more likely to experience addiction as an adult. The current review takes a developmental perspective and draws from animal and human studies to examine how compromised early experience, including insecure attachment, early abuse/neglect, and unresolved trauma, may influence the development of neurobiological pathways associated with addictions, ultimately increasing one’s susceptibility to addictions later in life. We approach this from three different levels: molecular, neuroendocrine and behavioral; and examine the oxytocin affiliation system, dopamine reward system, and glucocorticoid stress response system in this regard. Increased understanding of these underlying mechanisms may help identify key targets for early prevention efforts and inform needed intervention strategies related to both insecure attachment and addiction.